Stigma Influence of the Outcome (Experiences, Motivations, and Obstacles) Towards People with Mental Illness Problems in Babaka Public Health Centre, Lombok - I Putu Diatmika; Dany Karmila (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Mental health services are an important requirement for handling people with mental illness in the community, the high number of people with mental illness in West Nusa Tenggara and the achievement of services to them are currently a concern. Recurrence and drug withdrawal are a concern, one of the causes of the increasing number of relapse cases is the stigma against people with mental illness. The purpose of this study was to determine the effect of stigma on the outcome of people with mental illness in mental health services. The design of this study is a qualitative design carried out by in-depth interviews with 7 participants: 3 people with mental illness, 2 families or care givers, 1 Community Health Center Programmer and 1 medical doctor in public health centre to obtain information about stigma that affects outcomes (experiences, motivations and obstacles) of people with mental illness at Babakan Health Center, Mataram City, West Nusa Tenggara. The results of this study are that there is still a stigma that is felt by patients, both externalizing and internalizing stigma, so that it has an influence on patients in accessing mental health services.